2016
DOI: 10.3390/ijms17122138
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Epigenetic Regulators in Pancreatic Cancer and Their Clinical Implications

Abstract: Pancreatic cancer is one of the most aggressive human cancer types with a five-year survival less than 7%. Emerging evidence revealed that many genetic alterations in pancreatic cancer target epigenetic regulators. Some of these mutations are driver mutations in cancer development. Several most important mechanisms of epigenetic regulations include DNA methylation, histone modifications (methylation, acetylation, and ubiquitination), chromatin remodeling, and non-coding ribonucleic acids (RNAs). These modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 132 publications
0
31
0
Order By: Relevance
“…The epigenetic hypermethylation of the promoter CpG islands of tumor-suppressor genes, including APC, BRCA1, p16 INK4a can induce transcription inactivation during tumorigenesis, which is often observed in pancreatic cancer (6). Previous studies in pancreatic cancer reported frequent genetic abnormalities in Kras gene activation, but also in the epigenetic inactivation of p16 INK4a , p53 and SMAD4 in >50% of pancreatic ductal cancer cases (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic hypermethylation of the promoter CpG islands of tumor-suppressor genes, including APC, BRCA1, p16 INK4a can induce transcription inactivation during tumorigenesis, which is often observed in pancreatic cancer (6). Previous studies in pancreatic cancer reported frequent genetic abnormalities in Kras gene activation, but also in the epigenetic inactivation of p16 INK4a , p53 and SMAD4 in >50% of pancreatic ductal cancer cases (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, somatic mutations in the tumor protein p53 (TP53), SMAD family member 4 (SMAD4) and p16 genes can also contribute to the progression of pancreatic cancer (3)(4)(5). In addition to genetic mutations, modifications that are not due to changes in DNA sequence, including promoter hypermethylation, are often observed in pancreatic cancer cells (6). Epigenetic silencing and transcriptional inactivation due to hypermethylation in the 5'promoter regions of specific genes, including tumor-suppressor genes, for example hMLH1, BRCA1, p16 INK4a , can contribute to cancer progression (7).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies demonstrate that dysregulation of epigenetic regulators is essential for PDAC progression as well as for that of many other tumors [9]. Genomic deletions, mutations, and rearrangements frequently target genes encoding components of the chromatin remodeling complex (SWI/SNF), which have been identified in 10-15% of PDAC patients [10].…”
Section: Pdac From Genetics To Epigeneticsmentioning
confidence: 99%
“…The methylation of tumor suppressor genes is the best-characterized epigenetic event in several malignancies, including PDAC [11]. In fact, several genes such as APC, BRCA1, P16INK4a, P15INK4b, RARÎČ, and p73 are frequently methylated [10]. Recent studies have revealed that apparent DNA methylation occurred in critical signaling pathways in PDAC such as TGFÎČ, WNT, integrin, cell adhesion, and axon guidance signaling pathways [35].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Numerous reviews have deeply discussed and extensively summarized the recent advances of targeting epigenetics in cancer, in general, as well as in pancreatic cancer in particular [3,9,[16][17][18][19][20][21]. In this review, we focus on the transcriptional mechanisms of the most widely used epigenetic inhibitors in pancreatic cancer focusing on Bromodomain and Extraterminal (BET) and Histone Deacetylase (HDAC) inhibitors, which represent promising therapeutic options.…”
Section: Introductionmentioning
confidence: 99%